First Record of Tripartiella rhombi Shtein, 1961 (Ciliophora: Trichodinidae) in Iraq from Gills of the Common Carp Cyprinus Carpio: عائلة ترايكودينيدي) في العراق من غلاصم أسماك الكارب الإعتيادي Cyprinus Carpio - Abdul-Ameer, Kefah N.; Atwan, Fatima K. (Journal of Kerbala for Agricultural Sciences, 2018)
The examination of gills of the Cyprinus carpio Linnaeus, 1758 which were collected from Al-Graiat location on the Tigris river at Baghdad province during the period from July 2015 until the end of March 2016, resulted recording of the ciliophoran Tripartiella rhombi Shtein, 1961 for the first time in Iraq. The description and measurements of this parasite as well as its illustrations were given. With this record, two of Tripartiella species so far recorded from C. carpio as well as of all other Iraqi fishes.